ACT-107, a novel variant of AmpC β-lactamase from Enterobacter huaxiensis isolated from Neotropical leaf frog (Phyllomedusa distincta) inhabiting the Brazilian Atlantic Forest - Johana Becerra; Gabriel G. Araujo; Felipe Vasquez-Ponce; Faride Lamadrid-Feris; Nilton Lincopan (Journal of Global Antimicrobial Resistance, 2023)
ABSTRACT: Objectives: The aim of this study was to characterise a broad-spectrum cephalosporin-resistant AmpC-positive Enterobacter huaxiensis colonising the skin of a Neotropical frog (Phyllomedusa distincta) inhabiting the Brazilian Atlantic Forest. Methods: During a genomic surveillance study of antimicrobial resistance, we screened skin samples from P. distincta. Gram-negative bacteria growing on MacConkey agar plates supplemented with 2 µg/mL ceftriaxone were identified by matrix-assisted laser desorption/ionisation time-of-flight mass spectrometry. A cephalosporin-resistant E. huaxiensis was sequenced using the Illumina NextSeq platform. Genomic data were analysed using bioinformatics tools, whereas AmpC β-lactamase was characterised in depth by comparative analysis of amino acids, in silico modelling, and analysis of susceptibility to β-lactam antibiotics and combinations of β-lactamase inhibitors. Results: Whole-genome sequencing analysis revealed a novel variant of AmpC β-lactamase belonging to the ACT family, designated ACT-107 by NCBI. This variant contains 12 novel amino acid mutations within the ACT family, 5 in the signal peptide sequence (Ile2, Met14, Tyr16, Gly18 and Thr20), and 7 in the mature protein (Gln22, His43, Cys60, Thr157, Glu225, Ala252 and Asn310). In silico modelling showed that substitutions occurring in the mature chain are localised in the solvent-accessible surface of the protein, where they are not expected to affect the β-lactamase activity, as observed in the resistance profile. Strikingly, ‘not designated’ ACT variants from E. huaxiensis were clustered (> 96% identity) with ACT-107. Conclusion: Since E. huaxiensis has been isolated from human infection, ACT-107 requires surveillance and the attention of clinicians.